Careless love : the unmaking of Elvis Presley - Guralnick, Peter (Back Bay Books, 2000)
Recounts the second half of Elvis Presley's life, from his army service in 1958 Germany through his death in 1977, and focuses on his relationship with manager Colonel Tom Parker.